2016
DOI: 10.20510/ukjpb/4/i4/110643
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmaceutical Care Interventions on the Quality of Life of Group of Hypertensive Patients

Abstract: Studies have shown that pharmaceutical care interventions have the potential of reducing hospital stay and drug therapy problems; it can also improve patients' quality of life. The primary objectives of this study was to show how pharmaceutical care interventions could resolve actual drug therapy problems and prevent potential drug therapy problems; also, to assess the change in the quality of life of hypertensive patients after such interventions. An uncontrolled prospective study was done. Hypertensive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
1
5
1
Order By: Relevance
“…The same tool has been used in a Nigerian population before, but in the southern region of the country. 35 The findings of the study showed that there was an improvement in some of the domains of the QoL of the patients assessed at the end of the study: all domains in the MCS and bodily pain. Although the results of the present study revealed that there was no statistically significant difference between the study arms at the end of the study, clinical relevance cannot be ruled out.…”
Section: Qolmentioning
confidence: 90%
See 3 more Smart Citations
“…The same tool has been used in a Nigerian population before, but in the southern region of the country. 35 The findings of the study showed that there was an improvement in some of the domains of the QoL of the patients assessed at the end of the study: all domains in the MCS and bodily pain. Although the results of the present study revealed that there was no statistically significant difference between the study arms at the end of the study, clinical relevance cannot be ruled out.…”
Section: Qolmentioning
confidence: 90%
“…This study utilized the quality metric short form, a 12‐item tool, to assess the participants' QoL. The same tool has been used in a Nigerian population before, but in the southern region of the country 35 . The findings of the study showed that there was an improvement in some of the domains of the QoL of the patients assessed at the end of the study: all domains in the MCS and bodily pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is more evident in developed countries where entire organizations are shifting to a team-based approach to health care, which requires collaboration between all health care providers to provide the best, most efficient and most cost-effective services to patients. The role of each health care provider is being re-examined and redefined, so that patients can be seen in the timeliest manner and by the most qualified provider Smith et al [1].…”
Section: Introductionmentioning
confidence: 99%